Study on the Effect of Topical Pre-operative Nonsteroidal Anti-inflammatory Drugs in Maintaining Mydriasis during Small Incision Cataract Surgery - Hussain, Md Emdad (Community Based Medical Journal, 2023)
A prospective, randomized, double masked, single centered comparative study done in the Bangladesh Naval Ship Patenga, Chattogram, Bangladesh, from July 2021 to June 2022, to assess the clinical benefits and effectiveness of prophylactic pre-operative topical administration of NSAIDs in maintaining mydriasis during small incision cataract surgery. Thirty patients underwent small incision cataract surgery with intra ocular lens implantation were randomized to compare the efficacy of topical NSAIDs drops (Group-A) and placebo drops (Group-B) in maintaining peroperative mydriasis. Balanced salt solution containing non preservative adrenaline was used in all patients. Pupil size was measured prior to the corneal incision and after the completion of the operation. The two groups were analyzed with respect to the changes in pupillary diameter at the beginning and at the end of the operation. The change in pupil size was significantly different among the two groups at the end of the surgery. The mean vertical and horizontal diameter of the two groups were near about similar at the beginning of the surgery. Significant differences were seen after IOL implantation with the NSAIDs group having the larger mean diameter in both vertical (P=0.003) and horizontal (P=0.008) pupillary measurements at the conclusion of surgery. Topical NSAIDs has been shown to be a more effective inhibitor of meiosis during per operative uncomplicated small incision cataract surgery and provides a more stable mydriatic effect during surgery compared to the placebo group. CBMJ 2023 January: Vol. 12 No. 01 P: 22-26